Saline Sodic Soils of Lower Luni Basin - sharma, D.L. (Journal of Soil and Water Conservation, 1968)
Luni river is one of the important rivers of ,arid, region of western Rajasthan. It emerges from south western hills of Ajmer city and forms delta in sanchore tehsil.Bimal Ghose (1965) has recently reviewed the genesis of central Luni basin, where he has described the formation of Luni plains under humid climate in the recent past era but after the last glaciation in the pliestoscene period, the aridity set in as a result of which the prior drainage system gradually became disorganised and extensive deposition started in these older active river basins. The quality of underground' water of the area is reported to be saline and breackish (Sharma et al 1963). To know the potentialities and exploring the possibilities of better utilisation of the available resources, soil survey of lower Luni basin was undertaken.